Morphological responses, sensitivity and tolerance indices of four tropical trees species to drought and waterlogging - YULIANTI YULIANTI; DEDE J. SUDRAJAT (Society for Indonesian Biodiversity, 2016)
Yulianti, Sudrajat DJ. 2016. Morphological responses, sensitivity and tolerance indices of four tropical trees species todrought and waterlogging. Biodiversitas 17: 110-115. Indonesia’s climate model predicts an increase in threat of drought andwaterlogging in several areas. However, knowledge on variations between tropical forest tree species, i.e. Anthocephalus macrophyllus,Anthocephalus cadamba, Fagraea fragrans, and Magnolia champaca to drought and waterlogging stress are still limited, though theyare relevant to future development of forest ecosystem. The objective of this research is to investigate the adaptability of four potentialtree species to drought and waterlogging stress in a controlled greenhouse. The results showed that the adaptive responses of fourtropical tree species were different, according to the results, all species were more tolerant to waterlogging than to drought stress, whichcan be observed from morphological, seedling survival, stress tolerant and stress sensitivity indices. The waterlogging resistant in fourspecies followed the order of: A. cadamba > F. fragrans > A. macrophyllus, and > M. champaca, while for the drought resistant speciesfollowed the order: A. macrophyllus > A. cadamba > F. fragrans and > M. champaca.